2017
DOI: 10.3233/jae-170010
|View full text |Cite
|
Sign up to set email alerts
|

The drying quality and energy consumption of Chinese wolfberry fruits under electrohydrodynamic system

Abstract: The aim of this work is to study the drying quality of Chinese wolfberry fruits and the effect of energy consumption on the drying process using electrohydrodynamic (EHD) drying. The drying rate, nutrient content and energy consumption of the Chinese wolfberry fruits which were dried in an EHD system at two levels of electric field intensity and five levels of the discharge gap were investigated and compared against oven drying and the control. The results showed that the drying rate have no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Dinani et al found that the rehydration capacity of mushroom slices with EHD treatment was significantly higher than that of the oven dried at 60 °C, but the shear strength was lower than that of the oven dried at 60 °C [17]. We found that the drying rate of the Chinese wolfberry with EHD treatment was notably greater than that of the control in previous research [18,19]. Compared with the wire-to-plate and plate-to-plate electrode systems, a needle-to-plate electrode configuration had the highest drying rate, and the active ingredient was preserved well [18,19].…”
Section: Introductionsupporting
confidence: 41%
See 2 more Smart Citations
“…Dinani et al found that the rehydration capacity of mushroom slices with EHD treatment was significantly higher than that of the oven dried at 60 °C, but the shear strength was lower than that of the oven dried at 60 °C [17]. We found that the drying rate of the Chinese wolfberry with EHD treatment was notably greater than that of the control in previous research [18,19]. Compared with the wire-to-plate and plate-to-plate electrode systems, a needle-to-plate electrode configuration had the highest drying rate, and the active ingredient was preserved well [18,19].…”
Section: Introductionsupporting
confidence: 41%
“…We found that the drying rate of the Chinese wolfberry with EHD treatment was notably greater than that of the control in previous research [18,19]. Compared with the wire-to-plate and plate-to-plate electrode systems, a needle-to-plate electrode configuration had the highest drying rate, and the active ingredient was preserved well [18,19]. Multiple mathematical models can be used to describe the drying characteristics of Chinese wolfberry with EHD treatment, but the best models are slightly different under different drying conditions [18,19].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…It shows that the needle spacing can have a certain influence on the active ingredients inside the goji berry during the drying process. Yang et al reported that, compared with the hot-air drying, the polysaccharide content of goji berry dried electrohydrodynamically significantly increased [18]. Song et al found that under freeze-drying process, the flavonoid content of goji berry using distilled water pretreatment was much higher than that of sodium carbonate [26].…”
Section: Effect Of Different Needle Spacings On Average Drying Ratementioning
confidence: 99%
“…Bai et al dried the sea cucumber using electrohydrodynamic drying and found that the energy consumption under electrohydrodynamic drying is only 21.31% of the hot-air drying and the protein content is higher than that of the hot-air drying [16]. Previously, we used the electrohydrodynamic drying to dry the goji berry and achieved very satisfactory results [17,18].…”
Section: Introductionmentioning
confidence: 99%